KUTTAB; LEMBAGA PENDIDIKAN ISLAM KLASIK - Moh Toriqul Chaer (Lembaga Penelitian, Publikasi dan Pengabdian kepada Masyarakat (LP3M), STIT Islamiyah Karya Pembangunan Paron, Ngawi, Jawa Timur, 2015)
Historically, Islamic Education develops in line with the emergence of Islam itself. According to Harun Nasution, the development of Islamic history is divided into three periods, namely the classical period (650-1250 AD ), the middle period (1250-1800 AD ) and the modern period ( 1800 AD to present). Future classics, history of Islamic education is one of the fields of Islamic culture that is not widely known until now. This is due to the lack of original sources and incomplete writing material by the authors, both Muslims and non- Muslims. Almost all the authors attempt to illustrate that Islamic education as if it is a system which has been organized from primary to university level. This is a distorted picture of the rough and imposing stratification nomenclatur modern esistematik on a free and informal activities, where direct tidakberperan country until the advent of the madrasah. Kuttab as a learning system at the time of the Prophet than home Arqam ibn Arqam, has been known among the pre-Islamic Arabs. At first kuttab ( maktaab ) serves as a place providing writing and reading lessons for children, but when Islam began to grow, the lesson is emphasized in the Qur'an memorization method.